Troxerutin affects nephropathy signaling events in the kidney of type-1 diabetic male rats - Rana Keyhanmanesh; Gholamreza Hamidian; hajie lotfi; Zohre Zavari; Monireh Seyfollahzadeh; Afsane Ghadiri; Mehdi Ahmadi; Farzad Bahari; Fariba Mirzaei Bavil (Mashhad University of Medical Sciences, 2022)
Objective: Nephropathy is known to be the leading cause of kidney failure in diabetic patients. Troxerutin, as a flavonoid component, could provide a novel protective strategy in the prevention of diabetic nephropathy. A large number of reports on the salutary effects of troxerutin inspired us to investigate its effect on the nephropathy signaling events (i.e., expression of TGF-β, miRNA192, and SIP1) in type-1 induced diabetic rats.Materials and Methods: 50 male Wistar rats were divided into 5 groups including control group, sham group treated with troxerutin for 4 weeks, diabetic group induced by streptozotocin (STZ) injection, DI group including insulin-treated diabetic animals and DT group treated with troxerutin. Ultimately, rat kidneys were extracted, and the level of miR-192 (using qPCR), transforming growth factor-beta (TGF-β), and smad interacting protein 1 (SIP1) using an ELISA kit, was measured.Results: The level of TGF-β and miRNA192 significantly increased in the diabetic group. However, their expression levels decreased following the administration of troxerutin and insulin (p<0.05) compared to control group. SIP1 was down-regulated in the diabetic group, whereas a spike in the expression levels was observed after troxerutin administration compared to control and troxerutin groups (p<0.05). However, no significant difference was found in the effects of insulin and troxerutin on the level of miR-192, SIP1, and TGF- β.Conclusion: According to the previous literatures, during the progression of nephropathy, TGF-β represses SIP1 (the repression region in the collagen gene) by increasing the expression of miR-192. Ultimately, in this study, diabetes led to up-regulation of TGF-β while troxerutin proved to have a protective effect on the kidney by increasing SIP and lowering miR-192 levels.